Outcomes of Thrombectomy in Transferred Patients With Ischemic Stroke in the Late Window: A Subanalysis From the DEFUSE 3 Trial - Sarraj, Amrou (JAMA Neurol, 2019)
IMPORTANCE: Although thrombectomy benefit was maintained in transfer patients with ischemic stroke in early-window trials, overall functional independence rates were lower in thrombectomy and medical management–only groups. OBJECTIVE: To evaluate whether the imaging-based selection criteria used in the Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3 (DEFUSE 3) trial would lead to comparable outcome rates and treatment benefits in transfer vs direct-admission patients. DESIGN, SETTING, AND PARTICIPANTS: Subgroup analysis of DEFUSE 3, a prospective, randomized, multicenter, blinded–end point trial. Patients were enrolled between May 2016 and May 2017 and were followed up for 90 days. The trial comprised 38 stroke centers in the United States and 182 patients with stroke with a large-vessel anterior circulation occlusion and initial infarct volume of less than 70 mL, mismatch ratio of at least 1.8, and mismatch volume of at least 15 mL, treated within 6 to 16 hours from last known well. Patients were stratified based on whether they presented directly to the study site or were transferred from a primary center. Data were analyzed between July 2018 and October 2018. INTERVENTIONS OR EXPOSURES: Endovascular thrombectomy plus standard medical therapy vs standard medical therapy alone. MAIN OUTCOMES AND MEASURES: The primary outcome was the distribution of 90-day modified Rankin Scale scores. RESULTS: Of the 296 patients who consented, 182 patients were randomized (66% were transfer patients and 34% directly presented to a study site). Median age was 71 years (interquartile range [IQR], 60-79 years) vs 70 years (IQR, 59-80 years); 69 transfer patients were women (57%) and 23 of the direct group were women (37%). Transfer patients had longer median times from last known well to study site arrival (9.43 vs 9 hours) and more favorable collateral profiles (based on hypoperfusion intensity ratio): median for transfer, 0.35 (IQR, 0.18-0.47) vs 0.42 (IQR, 0.25-0.56) for direct (P = .05). The primary outcome (90-day modified Rankin Scale score shift) did not differ in the direct vs transfer groups (direct OR, 2.9; 95% CI, 1.2-7.2; P = .01; transfer OR, 2.6; 95% CI, 1.3-4.8; P = .009). The overall functional independence rate (90-day modified Rankin Scale score 0-2) in the thrombectomy group did not differ (direct 44% vs transfer 45%) nor did the treatment effect (direct OR, 2.0; 95% CI, 0.9-4.4 vs transfer OR, 3.1; 95% CI, 1.6-6.1). Thrombectomy reperfusion rates, mortality, and symptomatic intracranial hemorrhage rates did not differ. CONCLUSIONS AND RELEVANCE: In late-window patients selected by penumbral mismatch criteria, both the favorable outcome rate and treatment effect did not decline in transfer patients. These results have health care implications indicating transferring potential candidates for late-window thrombectomy is associated with substantial clinical benefits and should be encouraged. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02586415